The Hot Zone - Preston, Richard, 1954- (New York Anchor Books Doubleday, 1989)
A highly infectious, deadly virus from the central African rain forest suddenly appears in the suburbs of Washington, D.C. There is no cure. In a few days 90 percent of its victims are dead. A secret military SWAT team of soldiers and scientists is mobilized to stop the outbreak of this virus. The book tells this dramatic story, giving an account of the appearance of rare and lethal viruses and their "crashes" into the human race.
Keywords: Ebola virus disease